Inovasi pakaian ergonomis bagi pasien anak dengan terapi Intravena pada area lengan - Mujahidah Madani Salam; Sri Wening; Mohammad Adam Jerusalem (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
The main problem faced by pediatric patients undergoing intravenous (IV) therapy in the arm area is the difficulty in changing clothes due to the presence of an IV line, which reduces patient comfort and hinders the smooth delivery of care. This study aims to design ergonomic clothing for hospitalized children aged 5–9 years who are receiving IV therapy in the arm. The method used is Design Thinking, which consists of five stages: empathize, define, ideate, prototype, and test. The design process began with a needs assessment through interviews, observations, and literature review, followed by problem formulation, exploration of design ideas, prototype development, and product testing. The results show that the developed product is a two-piece garment consisting of a short-sleeved top and long pants, equipped with a special opening feature along the shoulder to the end of the sleeve, using snap button closures. Validation by three experts resulted in an average score of 89%, categorized as excellent, while product testing involving a patient, caregiver, and nurse yielded positive feedback. The designed clothing proved effective in facilitating patient clothing changes without removing the IV line or lowering the IV fluid bag from the IV pole, thereby improving the efficiency of nursing care, enhancing patient comfort, and supporting the smooth delivery of care during hospitalization.Published Date: 2026-07-22